Cell-Intrinsic Glycogen Metabolism Supports Early Glycolytic Reprogramming Required for Dendritic Cell Immune Responses - Thwe, Phyu M; Pelgrom, Leonard R; Cooper, Rachel; Beauchamp, Saritha; Reisz, Julie A; D'Alessandro, Angelo; Everts, Bart; Amiel, Eyal (Cell metabolism, 2017)
Dendritic cell (DC) activation by Toll-like receptor (TLR) agonists causes rapid glycolytic reprogramming that is required to meet the metabolic demands of their immune activation. Recent efforts in the field have identified an important role for extracellular glucose sourcing to support DC activation. However, the contributions of intracellular glucose stores to these processes have not been well characterized. We demonstrate that DCs possess intracellular glycogen stores and that cell-intrinsic glycogen metabolism supports the early effector functions of TLR-activated DCs. Inhibition of glycogenolysis significantly attenuates TLR-mediated DC maturation and impairs their ability to initiate lymphocyte activation. We further report that DCs exhibit functional compartmentalization of glucose- and glycogen-derived carbons, where these substrates preferentially contribute to distinct metabolic pathways. This work provides novel insights into nutrient homeostasis in DCs, demonstrating that differential utilization of glycogen and glucose metabolism regulates their optimal immune function.